2000
DOI: 10.1016/s1385-1101(00)00053-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of water temperature and oxygenation on the aerobic metabolic scope of Atlantic cod (Gadus morhua)

Abstract: Environmental influences (temperature and oxygenation) on cod metabolism and their impact on the ecology of this species were investigated. Limiting oxygen concentration curves (O 2 level ranging between 15 and 100% air saturation) were established at 2, 5 and 10°C. The standard metabolic rate (SMR), the maximum metabolic rate and the metabolic scope were then modelled as functions of temperature and/or oxygen saturation. The mean SMR at 2, 5 and 10°C were 19.8±4.9, 30.8±6.1 and 54.3±4.1 mg O 2 h −1 kg −1 , re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
159
3
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(182 citation statements)
references
References 41 publications
19
159
3
1
Order By: Relevance
“…These results are consistent with most published studies of fish species (Hammer 1995, Claireaux et al 2000, Lee et al 2003b, Fangue et al 2008, Yan et al 2012. The reduction in swimming performance with decreasing temperature could stem from changes in both the external and internal environment of the fish.…”
Section: Effect Of Temperature On Swimming Performancesupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with most published studies of fish species (Hammer 1995, Claireaux et al 2000, Lee et al 2003b, Fangue et al 2008, Yan et al 2012. The reduction in swimming performance with decreasing temperature could stem from changes in both the external and internal environment of the fish.…”
Section: Effect Of Temperature On Swimming Performancesupporting
confidence: 92%
“…Temperature and DO were selected as the environmental factors to be modified because they are the most frequently encountered and environmentally relevant physiological challenges (Randall & Brauner 1991, Claireaux et al 2000. The low temperature (10°C) selected in this study simulated the environment of the crucian carp in winter, whereas the hypoxic level simulated the extreme hypoxia situation in summer according to data on local water bodies in Chongqing, China.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between temperature dependent growth rates and aerobic scope may follow this pattern. Aerobic scope and growth rate were found related in a population of cod (Claireaux et al, 2000). Growth curves similarly shaped as in Fig.…”
Section: Trade-offs In Thermal Adaptation Setting Functional Limitssupporting
confidence: 56%
“…Temperature and oxygen are, respectively, potent controlling and limiting factors of fish metabolism, and they interact through their joint effects on MS (Fry 1971, Neill & Bryan 1991, Claireaux & Lagardère 1999. Using data from Chabot & Dutil (1999), Claireaux et al (2000) examined the consequences of reduced MS in Atlantic cod Gadus morhua exposed to hypoxia. These authors showed that a linear relationship could be established between the MS of cod and its growth.…”
Section: Christel Lefrançoismentioning
confidence: 99%